Effect of Rotating Burner Rim on Flame Stabilization: Blow-off and Flash Back - Abdul Wahhab, Hasanain A.; Aziz, A. Rashid A.; El-adawy, Mohammed; . Ismael, Mhadi A; ya, Firmans (International Journal of Engineering and Technology, 2018)
In present research, Schlieren photography has utilized to determine flame stabilization efficiency of methane–air mixture by tube burner method. The investigation is based on experiments carried out to identify the effect of varying the burner edge speed on the flame stabilization limits, and the blow-off and flash back limits of Schlieren cone at the high range methane-air premixing flows is studied. The flame was recorded using a high-speed digital camera and digital image processing techniques were applied on the captured frames. Two parameters are used in the method to characterize the flame stabilization on burner edge, the flame stabilization efficiency, and the flame stabilization coefficient. Data are presented for methane-air mixtures in wide ranges of equivalence ratios and burner edge speeds of (0.665 ≤ φ ≤ 1.733) and (0 ≤ Ne ≤ 38 r.p.m) respectively. The experimental results appear that rotation increases the flame stability coefficient, on the other hand, it’s decreasing the flame stability efficiency.